The administrative and supervisory practices in four American schools in the Philippines - Mangubat, Josephine G. 1930-
The aim of the study is to investigate certain administrative supervisory practices in four American schools in the Philippines. It purports to answer the question: What are the administrative and supervisory practices used at the Cebu American School, the Dole Philippines Elementary School at Cotabato, the American School at Makati, Rizal, and at Brent School in Baguio? The study reveals vital information about the education of foreign children as well as Filipino students.